Labour Relations and Modes of Employment - van Vliet, Olaf; Beblavy, Miroslav; Caminada, Koen; Domonkos, Stefan; Drahokoupil, Jan; Goudswaard, Kees; Koster, Ferry; Kurekova, Lucia; McQuinn, John; Munderlein, Maria; Murphy, Gavin; Myant, Martin; et al. (NEUJOBS, an European Research Consortium)
This Policy Brief contains policy implications on labour relations and modes of employment (Work Package 6), a collaborative EU-funded research project.
PUBLISHED
Keywords: Economics